2022
DOI: 10.1161/circresaha.122.320538
|View full text |Cite
|
Sign up to set email alerts
|

FMO2 (Flavin Containing Monooxygenase 2) Prevents Cardiac Fibrosis via CYP2J3-SMURF2 Axis

Abstract: BACKGROUND: Cardiac fibrosis is a common pathological feature associated with adverse clinical outcome in postinjury remodeling and has no effective therapy. Using an unbiased transcriptome analysis, we identified FMO2 (flavin-containing monooxygenase 2) as a top-ranked gene dynamically expressed following myocardial infarction (MI) in hearts across different species including rodents, nonhuman primates, and human. However, the functional role of FMO2 in cardiac remodeling is largely unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…By using analysis of transcriptomic data following renal IRI, it was discovered that the expression of one member of the FMO gene family, FMO2, was highly enriched in tubular cells and dynamically associated with renal injury and fibrotic remodeling. However, previous studies have shown that FMO2-mediated inhibition of TGF-β activity is independent of its enzymatic activity ( 18 ). Although non-enzymatic isoforms of FMO2 have been reported in humans and rats ( 30 - 32 ) and have been shown to influence the lifespan of the nematode Caenorhabditis elegans ( 33 ), their biological roles remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using analysis of transcriptomic data following renal IRI, it was discovered that the expression of one member of the FMO gene family, FMO2, was highly enriched in tubular cells and dynamically associated with renal injury and fibrotic remodeling. However, previous studies have shown that FMO2-mediated inhibition of TGF-β activity is independent of its enzymatic activity ( 18 ). Although non-enzymatic isoforms of FMO2 have been reported in humans and rats ( 30 - 32 ) and have been shown to influence the lifespan of the nematode Caenorhabditis elegans ( 33 ), their biological roles remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated dynamic changes in the expression of the flavin-containing monooxygenase (FMO) family between 2 h and 14 days post-ischemia reperfusion. A recent study has identified that FMO2 possesses a previously uncharacterized enzyme-independent antifibrotic activity via the cytochrome P450 2J3-SMAD ubiquitination regulatory factor 2 (SMURF2) axis ( 18 ). Particularly, FMO1 and FMO2, which are abundantly expressed in the kidney, are of significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4B further support that under the background of normal mice, the process of Pg -induced elevated plasma TMAO levels depends more on the oxidation of TMA in the liver rather than the generation of TMA in the intestine. Pg , Fn , and Sm groups exhibited a downregulation in FMO2 gene expression compared to the control group, which potentially indicates a general stress response of the liver to oral pathogenic bacterial infection ( Ni et al., 2022 ). In vitro TMAO exacerbates lipid accumulation, inflammation, and fibrosis in the liver ( Vallianou et al., 2019 ; Carpino et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…FMO2 is implicated in the recruitment of cytochrome p450 superfamily 2J3 (CYP2J3), blocking the CYP2J3/SMURF2 interaction and promoting the nuclear translocation of Smad2 (switching to its inactive form). For this reason, FMO2 has an anti-fibrotic role after cardiac injury, being a possible therapeutic target [ 204 ]. Li et al (2021) [ 205 ] also described a member of the TGF-β family, Left-right determination factor (Lefty1), with an anti-fibrotic function, since both in vitro and in vivo assays in mice show that Lefty1 reduces CFs proliferation and differentiation through the inhibition of phosphorylation of Smad2 and ERK1/2 after MI [ 205 ] ( Figure 4 B).…”
Section: Modulation Of Extracellular Matrix Deposition During Cardiac...mentioning
confidence: 99%